2023
DOI: 10.1017/s0142716423000048
|View full text |Cite
|
Sign up to set email alerts
|

Challenging deficit frameworks in research on heritage language bilingualism

Abstract: Recent years have seen an increased interest in the study of heritage language bilinguals. However, much of the research on heritage bilingualism is fraught with deficit framing. In this article, we demonstrate how many of the assumptions that underlie this growing field of research and the way that heritage speakers are positioned as research subjects reveal ideologies that center and value monolingualism and whiteness. We problematize a number of ways in which these ideologies commonly show up in the framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…There's really no straight answer to that” (Chinese–German HS, interview). These experiences contribute greatly to the confusing and frustrating feelings of “Americanness” and otherness that have been highlighted in work on HL identity (e.g., Higby et al., 2023). Constantly enduring these microaggressions can affect HSs’ sense of belonging, which one HS described in his interview as, “[feeling] like I was prepared for a world that doesn't exist.” The isolating effect that the HS identity can cause even with inner circles was also made clear by repeated comments along the lines of, “My family members don't understand how difficult it can be to navigate both worlds” (Korean HS, interview).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There's really no straight answer to that” (Chinese–German HS, interview). These experiences contribute greatly to the confusing and frustrating feelings of “Americanness” and otherness that have been highlighted in work on HL identity (e.g., Higby et al., 2023). Constantly enduring these microaggressions can affect HSs’ sense of belonging, which one HS described in his interview as, “[feeling] like I was prepared for a world that doesn't exist.” The isolating effect that the HS identity can cause even with inner circles was also made clear by repeated comments along the lines of, “My family members don't understand how difficult it can be to navigate both worlds” (Korean HS, interview).…”
Section: Resultsmentioning
confidence: 99%
“…There's really no straight answer to that" (Chinese-German HS, interview). These experiences contribute greatly to the confusing and frustrating feelings of "Americanness" and otherness that have been highlighted in work on HL identity (e.g., Higby et al, 2023). Constantly enduring these microaggressions can affect HSs' sense of belonging, which one HS described in his interview as, "[feeling] like I was prepared for a world that doesn't exist."…”
Section: Excerptmentioning
confidence: 99%
“…In recent years, this deficit-framing of heritage speakers' acquisition of their home language has faded in the literature, being replaced with more neutral terms such as "differential acquisition" , and "divergent attainment" . Furthermore, the notion of incompleteness has been challenged by some (e.g., Higby et al, 2023) and several studies have reported full acquisition of various aspects of the heritage language grammar (e.g., Guijarro-Fuentes and Schmitz, 2015;Schmitz et al, 2016;Schmitz and Scherger, 2019).…”
Section: Heritage Speakers As a Cognitively Distinct Bilingual Typementioning
confidence: 99%
“…The authors propose alternative methods and epistemological considerations to improve empirical rigor and promote diversity, inclusivity, and equity in the field. Higby et al (2023; next issue), in “Challenging deficit frameworks in research on heritage language bilingualism,” point out that research on heritage language bilingualism often uses deficit framing, which positions heritage speakers as research subjects and reinforces ideologies that center monolingualism and whiteness. The authors advocate for the use of frameworks such as usage-based linguistics and multicompetence that center the multidimensional experiences of bilinguals and embrace complexity and call for the research community to examine their designs and theories in order to dismantle the systems that marginalize heritage bilingualism in bilingualism research.…”
Section: What We’ve Learnedmentioning
confidence: 99%